STRUKTUR 4 MICROSTRIP PATCH ANTENA PANEL DENGAN GAP DAN BANDZ PADA FREKUENSI KERJA 2,4 GHz - Rohim Aminullah Firdaus, ; Yono Hadi Pramono, (Matematika dan Sains, 2011)
The aim of research was to fabricate and characterize the directional microstrip antenna which has structure 4 array with fiber subtrate for communication wi-fi 2.4 GHz. Fabrication was carried out using etching ferroclorit method. Antenna structure consisted of 4 simetry array. Characterization results showed that antenna could be applicated as directional antenna with VSWR value of 1.16. Radiation pattern was radial (vertical and horizontal) with gain of 18-20 dB and HPBW 450. 0.